Organometallic–Organic Hybrid Polymers Assembled from Pentaphosphaferrocene, Bipyridyl Linkers, and CuI Ions. Issue 23 (11th June 2018) - Moussa, Mehdi Elsayed; Welsch, Stefan; Lochner, Matthias; Peresypkina, Eugenia V.; Virovets, Alexander V.; Scheer, Manfred
Abstract : A multicomponent approach of the P n ligand complex [Cp*Fe(η 5 ‐P5 )] (1 : Cp* = η 5 ‐C5 Me5 ) with the ditopic organic linkers 4, 4′‐bipyridine (2 ) or trans ‐1, 2‐di(pyridine‐4‐yl)ethene (3 ) in the presence of Cu I salts of the anions [BF4 ] – and [PF6 ] – or the coordinating anion Br –, leads to the formation of four novel organometallic–organic hybrid polymers: the cationic 1D polymeric compounds [Cu4 Cp*Fe(µ3, η 5:1:1 ‐P5 )2 (µ, η 1:1 ‐C10 H8 N2 )4 (CH3 CN)4 ] n [BF4 ]4n (4 ) and [Cu4 Cp*Fe(µ3, η 5:1:1 ‐P5 )2 (µ, η 1:1 ‐C10 H8 N2 )4 (CH3 CN)4 ] n [PF6 ]4n (5 ) as well as the unique neutral threefold 2D → 2D interpenetrated networks [Cu2 Cl2 Cp*Fe(µ3, η 5:1:1 ‐P5 )(µ, η 1:1 ‐C12 H10 N2 )] n (6 ) and [Cu2 Br2 Cp*Fe(µ3, η 5:1:1 ‐P5 )(µ, η 1:1 ‐C10 H8 N2 )] n (7 ). Abstract : A mixed ligand approach using the polyphosphorus complex [Cp*Fe(η 5 ‐P5 )] with bipyridyl linkers and a variety of Cu I salts afforded four new hybrid coordination polymers (CPs): Two novel 1D cationic organometallic–organic CPs and two unique neutral threefold 2D → 2D parallelly interpenetrated networks.